2019
DOI: 10.1177/2399654419859365
|View full text |Cite
|
Sign up to set email alerts
|

Assessing states: Water service delivery and evolving state–society relations in Accra, Ghana and Cape Town, South Africa

Abstract: This paper analyzes water services in relation to trust in government, with insights for broader state–society relations. The work is based on a multi-year and multi-sited case study of underserved areas of Cape Town, South Africa and Accra, Ghana. The analysis reveals that water quality and satisfaction are statistically linked to trust in government in South Africa, but not in Ghana. As well, while indicators of water access and quality appear to be very good in South Africa, there is nonetheless deep contes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
1
7
0
1
Order By: Relevance
“…Our data suggest limited cross-sectoral dialogue, limited engagement between the authorities and communities, and integration of different departments in the production of strategies and programmes. The local municipality in the Agincourt HDSS struggles to continuously supply safe water; a common phenomenon in rural municipalities across South Africa [41,42]. This finding is consistent with other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Our data suggest limited cross-sectoral dialogue, limited engagement between the authorities and communities, and integration of different departments in the production of strategies and programmes. The local municipality in the Agincourt HDSS struggles to continuously supply safe water; a common phenomenon in rural municipalities across South Africa [41,42]. This finding is consistent with other studies.…”
Section: Discussionsupporting
confidence: 90%
“…A considerable number of studies have explored the links between urban services and state-society relations (Lemanski, 2019), including in the African context. As suggested by Harris (2020), research in a diversity of cities can challenge connections between service quality and trust in government and raise important questions concerning differences between different countries. Foucauldian views of the state as a symbolic entity with real effects generated through the practices of both state and non-state actors open the analytical view to the notion of ‘state effects’ (Mitchell, 1991) and processes of statisation (Painter, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Crucially, interviews with households in Bafatá and key informants showed that while localised state practices fundamentally shaped water infrastructure in Bafatá, these practices remained invisible to both state-society and state-donor relations. Like Harris (2020) suggests in the case of Ghana, there are few narratives among citizens directly connecting the state to water delivery in Bafatá. If anything, improvements in service appeared to feed perceptions of NGOs and donors’ roles in service provision.…”
Section: State Practices and Water Infrastructure In Bafatá: Unveilinmentioning
confidence: 99%
See 1 more Smart Citation
“…Debates about water fluoridation and chlorination reveal that community concerns are as much about faith in scientific experts, regulatory agencies, and governance as they are about the technical matter at hand. Broad considerations regarding trust in government, faith in democracy, and how this is connected to household water provision has only begun to be explored in the literature (Harris, 2020).…”
Section: Exposing Six Myths Of Household Water Insecuritymentioning
confidence: 99%